Aquí viene el que se poncha! - Kessler, Leonard P., 1920- ([New York, N.Y.] : Harper Arco Iris, 1995)
Bobby changes from an "easy out" to a game-winning hitter with the help of a friend and a lot of hard work.
Keywords: Baseball -- Fiction; Spanish language materials